Efficient synthesis of tetrahydrofurans with chiral tertiary allylic alcohols catalyzed by Ni/P-chiral ligand DI-BIDIME. Issue 6 (29th January 2021) - Mu, Yu; Zhang, Tao; Cheng, Yaping; Fu, Wenzhen; Wei, Zuting; Chen, Wanjun; Liu, Guodu
Abstract : Efficient nickel-catalyzed stereoselective asymmetric intramolecular reductive cyclization of O -alkynones with P -chiral bisphosphorus ligand DI-BIDIME is reported. Abstract : Efficient nickel-catalyzed stereoselective asymmetric intramolecular reductive cyclization of O -alkynones is reported. A P -chiral bisphosphine ligand DI-BIDIME was found to be effective for constructing versatile functionalized chiral tetrahydrofuran rings using triethylsilane as the reducing reagent. Practical synthesis of tetrahydrofurans with chiral tertiary allylic alcohols was achieved in high yields (99%), which have excellent stereoselectivity (>99 : 1 E / Z ) and enantioselectivity (>99 : 1 er) with a very broad substrate scope. A total of thirty-seven O -alkynones were synthesized and applied in this reaction successfully. This reaction can be scaled up to gram scale without loss of its enantioselectivity. The ligand effects and reaction mechanism are investigated in detail. Meanwhile, the developed method for tetrahydrofurans with chiral tertiary allylic alcohols enables the efficient synthesis of dehydroxycubebin and chiral dibenzocyclooctadiene skeletons, and is anticipated to find wider applications in organic synthesis and chemical biology; two new discovered reactions of O -alkynone with DI-BIDIME using different metal precursors would further expand new research fields, and attract more interesting explorations in the future.